Spatial and temporal variability in the production of propagules in mangrove forests in Southeastern Brazil - Cardoso, Carolina dos Santos; Chaves, Filipe de Oliveira; Soares, Mário Luiz Gomes (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2015)
In forests systems the adult plant distribution depends on the availability of propagules, recruitment and seedling development. Therefore the knowledge of the pattern of propagules production is important to understand this ecosystem. The data are from litterfall baskets in mangrove Guaratiba. Mangrove forests of Guaratiba presented propagules in the summer for Avicennia schaueriana and Rhizophora mangle, the last one with production throughout the year. Laguncularia racemosa presented the low production of propagules in the period of the study, with a representative peak just in 2012. The results with repeated measures ANOVA (3 factors – physiographic types, areas and years) shown to A. schaueriana significant difference between years, areas and for the interactions between years/physiographic types and years/physiographic types/areas. R. mangle showed significant difference between years, areas and for the interactions between physiographic type/areas. L. racemosa has no significant difference between the factors tested. Among the weather variables tested, no direct control of these parameters in the propagule production was detected. However, when considering the period between flowering and the release of propagules, it was observed that water storage in soil is important for the production of propagules of A. schaueriana.